Acute kidney injury in COVID-19: Considerations in pregnancy - Seema Chopra; Arshi Syal; Yajur Arya (Tzu Chi Medical Journal)
The clinical manifestations of COVID-19 are diverse with the involvement of different organ systems. Renal involvement is particularly noteworthy with acute kidney injury (AKI) being an important disease manifestation, particularly in pregnancy. Pregnancy itself serves as a high-risk condition for COVID-19 disease and a risk factor for deterioration, developing a more severe illness than nonpregnant women, and subsequent higher intensive care unit admission, oxygen therapy, and ventilatory support. There are reports in the literature highlighting the involvement of vital organs in pregnancy; however, data pertaining to AKI in pregnancy during COVID-19 are lacking in terms of risk factors, disease management, and outcomes. The entire spectrum of hormonal changes and adaptive mechanisms in pregnancy can be adversely affected by this viral infection. A literature search regarding AKI in COVID-19 in pregnancy was performed on PubMed, Scopus, Google Scholar, and ScienceDirect, and the relevant articles were selected. Our review highlights key issues pertaining to AKI in COVID-19 in pregnancy in an attempt to overcome, albeit partly, the scarcity of corroborative literature regarding the same.